Peran Kader Posyandu terhadap Tingkat Kunjungan Masyarakat - Hartini Haritani; Puspawan Hariadi; Ewisa Oktresia; Fitriwati Sovia; Baiq Maylinda Gemantari (Jurnal Kesmas Asclepius, 2022)
This study aims to describe the role of posyandu cadres on the level of visits by the users. The method used in this study is descriptive qualitative with a program evaluation approach. The results obtained from this study are that the number of visits by pregnant women, toddlers, and the elderly has increased. However, a strategy is needed to increase the interest of young women to utilize posyandu so that they can increase the number of visits by adolescents. In conclusion, the role of Posyandu cadres dramatically contributes to the health needs of small communities, especially in villages. Keywords: Cadres, Posyandu, Healthy